2020
DOI: 10.48550/arxiv.2005.11530
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Conformal bootstrap in Liouville Theory

Abstract: Liouville conformal field theory (denoted LCFT) is a 2-dimensional conformal field theory depending on a parameter γ ∈ R and studied since the eighties in theoretical physics. In the case of the theory on the 2-sphere, physicists proposed closed formulae for the n-point correlation functions using symmetries and representation theory, called the DOZZ formula (for n = 3) and the conformal bootstrap (for n > 3). In a recent work, the three last authors introduced with F. David a probabilistic construction of LCF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(39 citation statements)
references
References 47 publications
0
39
0
Order By: Relevance
“…Finally, let us emphasize that the massless sine-Gordon model is an essential example of a two-dimensional non-conformal perturbation of a CFT. For conformal field theories, a lot of recent progress has been made, in particular for the Ising model (see [10,11,33] and references therein) and for the Liouville CFT (see [31,37] and references therein). Moreover, we mention that models related to the massless Thirring model have also been studied in detail, in particular recently in the form of interacting dimers [28,29].…”
Section: Heuristics and Previous Resultsmentioning
confidence: 99%
“…Finally, let us emphasize that the massless sine-Gordon model is an essential example of a two-dimensional non-conformal perturbation of a CFT. For conformal field theories, a lot of recent progress has been made, in particular for the Ising model (see [10,11,33] and references therein) and for the Liouville CFT (see [31,37] and references therein). Moreover, we mention that models related to the massless Thirring model have also been studied in detail, in particular recently in the form of interacting dimers [28,29].…”
Section: Heuristics and Previous Resultsmentioning
confidence: 99%
“…for some constant C > 0 independent of 0 < ε 1. By Lemma 2.10 and the embedding f L p f B δ p,p (εZ 2 ) , inequality (32) implies that…”
Section: Difference Spaces and Besov Spaces On Latticementioning
confidence: 93%
“…The Sinh-Gordon model (in the limit case of zero mass m → 0) is an Integrable Quantum Field Theory see, e.g, [51,62] and has received considerable attention in the physics literature [58,68,69]. We remark also that a probabilistic approach developed to the Lioville model (V (ϕ) = exp(βϕ), m = 0) developed by Kupianen, Rhodes, Vargas and their coauthors has found remarkable success [32,42,43,44]. As of this moment we are not aware of a probabilistic construction of the Sinh-Gordon in the case m = 0, and giving such a construction appears to be an interesting and challenging problem.…”
Section: Introductionmentioning
confidence: 99%
“…Structure constants are model dependent. A highly non-trivial consequence of our work is a proof of the convergence of the series in q defining the Liouville CFT conformal blocks for almost all p (this fact was unknown except for the torus 1-point case by [GRSS20] and the sphere 4-point case in our previous work [GKRV20]).…”
Section: Introductionmentioning
confidence: 96%
“…Concerning Step 3, the importance of understanding the spectral analysis of the Hamiltonian of LCFT was stressed in physics by Teschner in [Te01]. This was recently mathematically settled in our previous work [GKRV20] using tools from scattering theory, semigroups and probability, allowing us to prove the conformal bootstrap for the sphere.…”
Section: Introductionmentioning
confidence: 99%

Segal's axioms and bootstrap for Liouville Theory

Guillarmou,
Kupiainen,
Rhodes
et al. 2021
Preprint
Self Cite